Pitch perfect : raising capital for your startup - Kamps, Haje Jan (Apress, 2020)
You have a home-run startup idea and a whip-smart team to execute it. Everything should be in place to kick-start your company and secure funding. However, there is one more step that can make or break the entire deal: the pitch. Founders everywhere struggle to nail the perfect pitch to garner VC backing, and this book is here to help. Pitch Perfect by Haje Jan Kamps expertly teaches you how to tell your startups story. To raise venture capital, it is absolutely crucial that your foundation is a story that is accessible, compelling, and succinct. Kamps uses his invaluable experiential knowledge to guide you through your presentation, from slide deck specifics to storytelling details to determining a fundamental philosophy for your business. In the process of creating and formulating a pitch deck and the story to go with it, founders often discover deep flaws in their business idea. Perhaps the market is non-existent. It could be that the "problem" isnt worth solving. Maybe the idea is so simple that it would be too easy to copy. Maybe its already been done, or the team simply is not up to the job. Pitch Perfect has all of those bases covered so that you can excel. How do you convince an institutional investor to part with their money and fund your company? The small block of time you are given for a pitch holds your startups future in its grasp. Learn how to craft your startup story in a way that will get people to lean into your message with Pitch Perfect. Your dream is only one pitch away